Evaluation of sunflower germplasm against charcoal rot : Evaluation of sunflower germplasm against charcoal rot - NAVKIRAN KAUR; JASWINDER KAUR; ANNA GOEL; AMANDEEP SINGH; PANKAJ SHARMA; P S SANDHU; VINEETA KAILA; S S KANDHOLA (Journal of Oilseeds Research, 2023)
A total of 85 sunflower genotypes were evaluated against charcoal rot by imposing drought conditions during flowering. Disease assessment was done by taking inner lesion length that varied from 0.70 cm 47.82 cm and the average inner lesion length of non-irrigated trials was more as compared to irrigated trials. The disease spread was more prominent in drought conditions that affect the plant height, root width as well as the head diameter.